2001
DOI: 10.1074/jbc.m102596200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Conversion of Hemocyanin to Phenoloxidase by Horseshoe Crab Antimicrobial Peptides

Abstract: Arthropod hemocyanins and phenoloxidases serve different physiological functions as oxygen transporters and enzymes involved in defense reactions, respectively. However, they are equipped with a structurally similar oxygen-binding center. We have shown that the clotting enzyme of the horseshoe crab, Tachypleus tridentatus, functionally converts hemocyanin to phenoloxidase by forming a complex without proteolytic cleavage (Nagai, T., and Kawabata, S. (2000)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 56 publications
4
109
0
3
Order By: Relevance
“…Nagai et al documented that hemocyanin of horseshoe crab Tachypleus tridentatus could be functionally converted into a phenoloxidase-like enzyme by the clotting enzyme and by chitin-binding antimicrobial peptides [4,5]. Treating hemocyanins from crustacean with SDS resulted in an opening of the entrance to the active site of the protein for bulkyphenolic compounds [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nagai et al documented that hemocyanin of horseshoe crab Tachypleus tridentatus could be functionally converted into a phenoloxidase-like enzyme by the clotting enzyme and by chitin-binding antimicrobial peptides [4,5]. Treating hemocyanins from crustacean with SDS resulted in an opening of the entrance to the active site of the protein for bulkyphenolic compounds [6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides being an important respiratory protein, the HMC plays a crucial role in frontline innate immune response during which it is proteolytically processed by serine proteases to activate its prophenoloxidase (PPO) activity. 29 Our recent study has shown , unpublished). Indeed, we have also identified a prophenoloxidase activating enzyme, PPOA (HpF149), which was strongly upregulated in the hepatopancreas from 3 hpi to reach a peak at 6 hpi ( Figure 4b).…”
Section: à3mentioning
confidence: 99%
“…The resulting PPO activity of HMC catalyses the oxidation of phenols to quinones, thereby inducing melanisation to oxidatively kill the invading microbe. 29 Furthermore, HMC also releases a C-terminal peptide that has antimicrobial activity. and tissue remodelling.…”
Section: à3mentioning
confidence: 99%
“…detergents and alcohols) or polypeptides (e.g. antimicrobial peptides, serine proteinase precursors) (Asada et al, 1993;Decker et al, 2001;Nagai et al, 2001;Nagai and Kawabata, 2000), PAP-1 and SPHs could simply bind to proPO, change its conformation, and yield PO activity without any proteolysis. To test this possibility, we first incubated PAP-1 with an irreversible serine proteinase inhibitor, APMSF, to block its amidase activity.…”
Section: Significance Of Proteolytic Cleavage In Propo Activationmentioning
confidence: 99%